1996
DOI: 10.1111/j.1476-5381.1996.tb15289.x
|View full text |Cite
|
Sign up to set email alerts
|

KW‐4679‐induced inhibition of tachykininergic contraction in the guinea‐pig bronchi by prejunctional inhibition of peripheral sensory nerves

Abstract: Sensory mechanisms play an important role in the vagal regulation of tracheobronchial smooth muscle tone. We examined the effect of KW‐4679, an anti‐allergic drug, on guinea‐pig tachykinin‐mediated contractile responses induced by electrical field stimulation (EFS) in guinea‐pig bronchial muscles. EFS (8 Hz, 0.5 ms, 15 V, for 15 s) evoked biphasic contractile responses in the guinea‐pig isolated main bronchus in the presence of 5 μm indomethacin. The contractions consisted of a fast phase of an atropine‐sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The antihistaminic action of olopatadine is unlikely to be involved in the inhibition by this drug of the sneeze response, as the conventional antihistamines did not affect the response (Table 1). It is reported that the inhibition by olopatadine of the tachykininergic contraction of isolated guinea pig bronchi was diminished by the SKCa channel inhibitors and not by naloxone (2). These results suggest that olopatadine inhibits the sneezing response by suppressing the tachykinin release presynaptically through the activation of the SKCa channels and not the opioid receptors.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…The antihistaminic action of olopatadine is unlikely to be involved in the inhibition by this drug of the sneeze response, as the conventional antihistamines did not affect the response (Table 1). It is reported that the inhibition by olopatadine of the tachykininergic contraction of isolated guinea pig bronchi was diminished by the SKCa channel inhibitors and not by naloxone (2). These results suggest that olopatadine inhibits the sneezing response by suppressing the tachykinin release presynaptically through the activation of the SKCa channels and not the opioid receptors.…”
mentioning
confidence: 49%
“…The previous in vitro study (2) demonstrated that olopatadine, which did not affect the contraction induced by exogenous substance P (SP) or neurokinin A, inhibited the tachykininergic contraction induced by electrical field stimulation (EFS) in guinea pig bronchial muscles without affecting the cholinergic contraction. Moreover, the inhibitory effect of olopatadine on the tachykininergic contraction was suppressed by the small conductance Ca 2+ -activated K + (SKCa) channel blocker, apamin or scyllatoxin.…”
mentioning
confidence: 99%
“…Apamin or scyllatoxin per se did not influence the slow phase contraction. These results suggest that olopatadine preferentially inhibits the release of tachykinins from the bronchial sensory nerves through activation of small conductance Ca 2+ -activated K + channel (41). Electrical stimulation of the vagus nerve in atropine-treated and propranolol-treated guinea pigs under anesthetization caused a 38.1% decrease in Cdyn, which was suppressed by the combination of (±)-CP-96,345 and SR 48968.…”
Section: -2 Mode Of Action 2-2-1 Histamine H1-receptor Antagonistimentioning
confidence: 78%
“…The fast phase and slow phase of contraction are mediated by acetylcholine released from parasympathetic nerves and tachykinins released from unmyelinated sensory nerves, respectively (40). Ikemura et al examined the effect of olopatadine on contractile responses induced by EFS in guinea pig bronchial muscles (41). EFS (8 Hz, 0.5 ms, 15 V, for 15 s) evoked biphasic contractile responses in the guinea pig main bronchus in the presence of indomethacin to prevent the formation of contractile prostaglandins.…”
Section: -2 Mode Of Action 2-2-1 Histamine H1-receptor Antagonistimentioning
confidence: 99%
“…KW-4679 also inhibits the production and/or release of PAF and leukotriene B4 (LTB4) in human neutrophils (8). KW-4679 reduces the electrical field stimulation induced tachykininergic contraction through reduction in the release of transmitters from sensory nerve endings in the isolated guinea pig main bronchus (9). Receptor binding studies have shown this compound to be a hista mine H1-receptor antagonist with a K; value of 16 nM (10).…”
mentioning
confidence: 99%